THE IMPORTANCE OF TRANSPERANCY IN SUSTAINABLE DEVELOPMENT FOR NATION BUILDING: An Expository Analysis from Islamic Thought - Abubakar Ibrahim Usman; Jamila Muhammad Anka (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
Sustainable development for nation building is not a new concept to Islam, sustainable development principles have existed for centuries in the Glorious Qur'an and the Hadith. However, sustainable development concept may have been recently adopted for government and civic society in Islamic world. The Islamic thought embraces that everything on earth is created for humanity and Allah's award to people. Islam allows the consumption of the natural environment without involving unnecessary destruction. Islamic thought views that human activities should support environment, and protection of people’s rights, and needs ensuring that human activities do not compromise the essentials of social, economic and natural systems either now or in the future. The aim of this study is to discover the application of Islam in sustainable development debate. Sustainable development in the context of Islamic concept is taken as an opportunity to refresh the relationship between human being and the nation building. This paper will also discuss the role of transparency and accountability in building good governance. With Iḥsan and Taqwa based on Iman, people can control, manage and report their actions, although there are no punishments or responsibility questions from others. The principles of transparency and accountability in the Qur’an guarantee social control and report, wide public participation, kind public service, self-honest, self-control and self-responsibility so that various forms of distortion such as corruption or discrimination can be avoided and controlled.